2021
DOI: 10.1136/postgradmedj-2020-139241
|View full text |Cite
|
Sign up to set email alerts
|

High-stakes examinations during the COVID-19 pandemic: to proceed or not to proceed, that is the question

Abstract: The COVID-19 pandemic has disrupted education-related activities, including the conduct of examinations. We review the literature regarding high-stakes examinations during the pandemic, discuss the decision-making process of whether to proceed with a high-stakes examination and share published experiences in conducting high-stakes examinations during the pandemic. We illustrate our own recent experiences of decision-making and conduct of our high-stakes gastroenterology licencing examinations during the height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Results indicated that the overall satisfaction of both examiners and students with the conducted assessment was high with that of the examiners' being higher. Similar results were obtained by Tan et al [17]. On the other hand, concerns about the number of questions used, the mark allocated for the final assessment, technical problems and poor nonverbal communication on video-conferencing were mainly disliked by a certain fraction of students (30.7%) and might have contributed in their non-satisfaction.…”
Section: Plos Onesupporting
confidence: 84%
“…Results indicated that the overall satisfaction of both examiners and students with the conducted assessment was high with that of the examiners' being higher. Similar results were obtained by Tan et al [17]. On the other hand, concerns about the number of questions used, the mark allocated for the final assessment, technical problems and poor nonverbal communication on video-conferencing were mainly disliked by a certain fraction of students (30.7%) and might have contributed in their non-satisfaction.…”
Section: Plos Onesupporting
confidence: 84%
“…Another major impact of the COVID-19 pandemic and online teaching-learning is on the conduct of assessment for the students (Tan, et al,2021). With a complete shift to online mode, newer modalities are now being developed to conduct examinations for the students and their assessments.…”
Section: Challenges For Medical Professors and Teachersmentioning
confidence: 99%
“…We argue that part of the sacredness – part of the obligatory features and qualifications – of examinations is related to the naturalization of a scripted and regulated performance carried out by a complex network of actors. Although there has been a rise of alternative forms of examination in past decades, the width, speed and the range of subjects that the pandemic caused to change, moving even high-stake examinations into digital, remote and open-book formats, are unprecedented (Boursicot et al, 2020; Sam et al, 2020; Tan et al, 2021).…”
Section: Examinations: Obligatory Points Of Passage Sacred Rituals and Choreographiesmentioning
confidence: 99%
“…They often include continuous elements of (more or less thought-through) improvisation. Constant adjustments and workarounds are needed as plans meet practices in the shaping of emergency examination realities (see also Boursicot et al, 2020; Tan et al, 2021). Responses have ranged from temporarily abandoning examinations in favour of teacher assessments, to retaining conventional face-to-face examinations by ‘controlling’ the risk of Covid-19 through the introduction of elaborate protocols around distancing and sanitization.…”
Section: Conclusion: the Show Must Go On – The ‘Thinging’ Of Examinationsmentioning
confidence: 99%